2010
DOI: 10.1111/j.1365-2567.2009.03232.x
|View full text |Cite
|
Sign up to set email alerts
|

The Toll‐like receptor 2 (TLR2) ligand FSL‐1 is internalized via the clathrin‐dependent endocytic pathway triggered by CD14 and CD36 but not by TLR2

Abstract: Little is known of how Toll-like receptor (TLR) ligands are processed after recognition by TLRs. This study was therefore designed to investigate how the TLR2 ligand FSL-1 is processed in macrophages after recognition by TLR2. FSL-1 was internalized into the murine macrophage cell line, RAW264.7. Both chlorpromazine and methyl-beta-cyclodextrin, which inhibit clathrin-dependent endocytosis, reduced FSL-1 uptake by RAW264.7 cells in a dose-dependent manner but nystatin, which inhibits caveolae- and lipid raft-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
6
21
1
Order By: Relevance
“…Fourth, Cy2-SitC-His was internalized readily in MKs or MM6 cells, in a TLR2-independent way. Our findings confirm the data of Shamsul and colleagues, who showed that the uptake of FSL-1, a known TLR2 ligand, is not dependent on the presence of TLR2 (41). Stimulation of TLR2 in MK cells is accompanied by an increase of its transcription (25), and here we show that the increase of transcription correlated with an increase of TLR2, which reached a maximum after 90 min of stimulation; longer incubation times (180 min) (data not shown) did not lead to a further increase of mainly intracellular TLR2.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Fourth, Cy2-SitC-His was internalized readily in MKs or MM6 cells, in a TLR2-independent way. Our findings confirm the data of Shamsul and colleagues, who showed that the uptake of FSL-1, a known TLR2 ligand, is not dependent on the presence of TLR2 (41). Stimulation of TLR2 in MK cells is accompanied by an increase of its transcription (25), and here we show that the increase of transcription correlated with an increase of TLR2, which reached a maximum after 90 min of stimulation; longer incubation times (180 min) (data not shown) did not lead to a further increase of mainly intracellular TLR2.…”
Section: Discussionsupporting
confidence: 82%
“…Where TLR2 is localized intracellularly is unknown, but most likely it is bound to the Golgi apparatus or the vesicular compartments of the endosomal pathway (11,23,34,36,41,49). TLR4 has been described to cycle between the Golgi 3 Cys.…”
Section: Discussionmentioning
confidence: 99%
“…Although the internalization of Pam2IDG was reduced in TLR2KO BMDCs and by an anti-TLR2 Ab, we cannot exclude the possibility that unknown receptors may contribute to the endocytosis of Pam2IDG. In contrast to our findings, another group (38) found that the TLR2 ligand FSL-1 was internalized via a clathrin-dependent and TLR2-independent endocytosis pathway. Their data suggested that CD14 and CD36 were responsible for the internalization of FSL-1.…”
Section: Discussioncontrasting
confidence: 55%
“…P<0.05 was considered as statistically significant (*), P<0.01 as highly significant (**), and P< 0.001/P< 0.0001 were considered as extremely significant (***/****). is controlled by clathrin-dependent endocytosis mechanism [26]. Therefore, to assess the role of TLR2-ligand internalization in MMP-9 induction, THP-1 cells were pretreated with 10µM of Chlorpromazine, an inhibitor of clathrin-dependent endocytosis and 1mM methyl-β-cyclodextrin (MBCD), an inhibitor of clathrin-independent endocytosis followed by treatment with Pam3CSK4 and incubation for 24 hrs.…”
Section: Effect Of Endocytosis Inhibitor On Pam3csk4-mediated Mmp-9 Imentioning
confidence: 99%